2016
DOI: 10.1038/srep23146
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HSV-1 Replication by Gene Editing Strategy

Abstract: HSV-1 induced illness affects greater than 85% of adults worldwide with no permanent curative therapy. We used RNA-guided CRISPR/Cas9 gene editing to specifically target for deletion of DNA sequences of the HSV-1 genome that span the region directing expression of ICP0, a key viral protein that stimulates HSV-1 gene expression and replication. We found that CRISPR/Cas9 introduced InDel mutations into exon 2 of the ICP0 gene profoundly reduced HSV-1 infectivity in permissive human cell culture models and protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
109
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 43 publications
5
109
2
1
Order By: Relevance
“…First, we demonstrated the introduction of endonuclease-induced mutations in latent HSV genomes in neurons, the biologically relevant cell type. Previously, we and others showed that HSV infection is inhibited in the presence of HSV-specific endonucleases in vitro (12, 13, 25). We further demonstrated in vitro that HSV-specific HEs could mediate mutagenesis of latent HSV and limit subsequent reactivation (13).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First, we demonstrated the introduction of endonuclease-induced mutations in latent HSV genomes in neurons, the biologically relevant cell type. Previously, we and others showed that HSV infection is inhibited in the presence of HSV-specific endonucleases in vitro (12, 13, 25). We further demonstrated in vitro that HSV-specific HEs could mediate mutagenesis of latent HSV and limit subsequent reactivation (13).…”
Section: Discussionmentioning
confidence: 98%
“…We further demonstrated in vitro that HSV-specific HEs could mediate mutagenesis of latent HSV and limit subsequent reactivation (13). However, none of these previous studies were done in neuronal cells (12, 13, 25), and the demonstration that endonucleases can also mutate HSV in sensory neurons, the relevant cell type for HSV latency, provides support for evaluating this approach in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However in rare cases, HSV-1 can replicate in the central nervous system causing encephalitis. We and several other laboratories applied CRISPR/Cas9 to HSV-1 (Roehm et al, 2016; van Diemen et al, 2016; Li et al, 2017). We found that CRISPR/Cas9 introduced InDels into the HSV-1 ICP0 gene reducing viral infectivity in human cell cultures and protecting them against HSV-1 infection.…”
Section: Recent Applications Of Crisprmentioning
confidence: 99%
“…We found that CRISPR/Cas9 introduced InDels into the HSV-1 ICP0 gene reducing viral infectivity in human cell cultures and protecting them against HSV-1 infection. CRISPR targeting ICP0 plus the ICP4 or ICP27 completely abrogated HSV-1 infection indicating that CRISPR/Cas9 has the potential to be developed as a novel and specific therapeutic and prophylactic tool for HSV-1 disease (Roehm et al, 2016). …”
Section: Recent Applications Of Crisprmentioning
confidence: 99%
“…CRISPR/Cas9 was efficiently used to cleave the genome of DNA viruses such as Epstein-Barr virus in human cells and to target herpesvirus genomes in herpesvirus induced diseases such as lymphomas and adenocarcinomas [62][63][64][65][66][67]. The RNAtargeting CRISPR/C2c2 system, which is guided by a single crRNA and has ribonuclease function, could be designed to knock down specific mRNA or cleave the single-stranded viral RNA that carries complementary protospacers, establishing CRISPR/C2c2 system as a novel RNA-targeting strategy [68,69].…”
Section: Possible Therapeutic Applicationsmentioning
confidence: 99%